The Tradition of the Trojan War in Homer and the Epic Cycle. - Burgess, Jonathan S. (Johns Hopkins University Press NetLibrary, Inc. [distributor], 2003)
Although the Iliad and Odyssey narrate only relatively small portions of the Trojan War and its aftermath, for centuries these works have overshadowed other, more comprehensive narratives of the conflict, particularly the poems known as the Epic Cycle. In The Tradition of the Trojan War in Homer and the Epic Cycle, Jonathan Burgess challenges Homer's authority on the war's history and the legends surrounding it, placing the Iliad and Odyssey in the larger, often overlooked context of the entire body of Greek epic poetry of the Archaic Age. He traces the development and transmission of the Cyclic poems in ancient Greek culture, comparing them to later Homeric poems and finding that they were far more influential than has previously been thought.